2017
DOI: 10.5812/ijp.7752
|View full text |Cite
|
Sign up to set email alerts
|

Duckett versus Modified Bracka Technique for Proximal Hypospadias Repair A 10-Year Experience

Abstract: Background: There are various techniques for treatment of proximal hypospadias disease.Surgical correction is often associated with complications. Proximal hypospadias can be repaired by Duckett or Bracka two-stage repair procedure. This study was to evaluate the outcomes, complications and long term follow-up of these two techniques in our referral hospital. Methods: From January 2006 to January 2015 totally 1550 cases of hypospadias were diagnosed in our hospital, of which 164 patients with high type hypospa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Other causes of hypospadias in children include genetic polymorphisms, identified in FGF8 and FGFR2 genes, that were observed in a minor share of cases. Since the development of male reproductive organs is an AR-dependent process, it can be suggested that polymorphisms, identified in FGF8 and FGFR2 genes in boys with hypospadias, can prevent AR-responses during the development of the urethra (Beleza-Meireles et al, 2007; Sadeghi et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Other causes of hypospadias in children include genetic polymorphisms, identified in FGF8 and FGFR2 genes, that were observed in a minor share of cases. Since the development of male reproductive organs is an AR-dependent process, it can be suggested that polymorphisms, identified in FGF8 and FGFR2 genes in boys with hypospadias, can prevent AR-responses during the development of the urethra (Beleza-Meireles et al, 2007; Sadeghi et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The two-stage approach separated VC correction and reconstruction of the urethral plate from urethroplasty, simplifying proximal hypospadias repairs with a lower complications rate, and has become the preferred method for many surgeons ( 7 , 8 ). The comparative studies of these two techniques indicate a higher complication rate of TPIFU ( 9 , 10 ). During the past decades, researchers have modified the surgical technique of TPIFU in order to improve the success rate.…”
Section: Introductionmentioning
confidence: 99%
“…The two-stage approach separated VC correction and reconstruction of the urethral plate from urethroplasty, simplifying proximal hypospadias repairs with a lower complications rate, and has become the preferred method for many surgeons [7,8]. The comparative studies of these two techniques indicate a higher complication rate of TPIFU [9,10]. However, two-stage repair commits patients to at least two procedures, while a second procedure might be avoided in some patients who undergo a singlestage approach.…”
Section: Introductionmentioning
confidence: 99%